2018
DOI: 10.1016/j.jcin.2018.01.239
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Pulmonary Valve Replacement With the Melody Valve in Small Diameter Expandable Right Ventricular Outflow Tract Conduits

Abstract: In this preliminary experience, TPVR with the Melody valve into expandable small diameter conduits was feasible and safe, with favorable early and long-term procedural and hemodynamic outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…There are a growing number of studies of TPVR in smaller patients with smaller conduits and bioprosthetic valves. These studies have demonstrated the ability to expand small diameter conduits up to 18, 20 and even 22 mm with similar technical success rates and adverse event profiles to studies in larger patients . In this current analysis, three patients with nominal conduit diameters <16 mm were successfully implanted and all were dilated to greater than 120% of the original conduit size and implanted with 18 mm or 20 mm delivery systems.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…There are a growing number of studies of TPVR in smaller patients with smaller conduits and bioprosthetic valves. These studies have demonstrated the ability to expand small diameter conduits up to 18, 20 and even 22 mm with similar technical success rates and adverse event profiles to studies in larger patients . In this current analysis, three patients with nominal conduit diameters <16 mm were successfully implanted and all were dilated to greater than 120% of the original conduit size and implanted with 18 mm or 20 mm delivery systems.…”
Section: Discussionmentioning
confidence: 80%
“…These studies have demonstrated the ability to expand small diameter conduits up to 18, 20 and even 22 mm with similar technical success rates and adverse event profiles to studies in larger patients. [15][16][17] In this current analysis, three patients with nominal conduit diameters <16 mm were successfully implanted and all were dilated to greater than 120% of the original conduit size and implanted with 18 mm or 20 mm delivery systems. If this practice continues to grow, it will be important to have a complementary valve option that functions well in smaller conduits and bioprosthetic valves.…”
Section: Discussionmentioning
confidence: 99%
“…Young age at time of RVOT conduit or BPV implantation is associated with earlier reintervention in many studies, but little is known about the relationship between age and outcomes after TPVR. This study compared pediatric patients with adults who underwent Melody TPVR in three multicenter prospective trials.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the available conduits ( Table 1 ) can meet the clinical needs in most countries, and re-thoracotomy for conduit replacement is no longer a high-risk operation for cardiac surgeons. Moreover, trans-catheter pulmonary valve replacement (TPVR) has been proven to be a safe and effective therapeutic for failed pulmonary conduits ( 34 ). Therefore, our current task is to improve the durability and prolong the life of the valved conduit for RVOT reconstruction.…”
Section: Historymentioning
confidence: 99%